Evidence for microplastics contamination of the remote tributary of the Yenisei River, Siberia - The pilot study results - Frank, Yuliya A.; Vorobiev, Danil S.; Kayler, Olga A.; Vorobiev, Egor D.; Kulinicheva, Ksenia S.; Trifonov, Anton A.; Hunter, Soliman Tina (Water, 2021)
This study is a pioneering attempt to count microplastics (MPs) in the Yenisei River system to clarify the role of Siberian Rivers in the transport of MPs to the Arctic Ocean. The average MPs content in the surface water of the Yenisei large tributary, the Nizhnyaya Tunguska River, varied from 1.20 ± 0.70 to 4.53 ± 2.04 items/m3, tending to increase along the watercourse (p < 0.05). Concentrations of MPs in bottom sediments of the two rivers were 235 ± 83.0 to 543 ± 94.1 with no tendency of downstream increasing. Linear association (r = 0.952) between average organic matter content and average counts of MPs in bottom sediments occurred. Presumably MPs originated from the daily activities of the in-situ population. Further spatial-temporal studies are needed to estimate the riverine MPs fluxes into the Eurasian Arctic seas.